Evaluation of Chiffon Cake Quality Using Stevia as a Sugar Substitute (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) study the physical quality and sensory qualities of chiffon cakes using stevia and 2) compare the differences in quality between chiffon cakes using stevia and granulated sugar. Three general chiffon cake recipes were studied and their sensory qualities in terms of appearance, color, aroma, taste, texture, and overall liking were assessed using a 9-Point Hedonic Scale with five experts. The results showed that recipe C 03 received the highest preference. The recipes were then studied for the quality of chiffon cakes using stevia instead of all granulated sugar in the product. The amount of stevia was studied at five levels: original recipe, mixed with 16 grams of stevia, mixed with 32 grams of stevia, mixed with 48 grams of stevia, and mixed with 64 grams of stevia. The sensory preferences of 60 general subjects were tested and it was found that the recipe mixed with 32 grams of stevia received the highest preference. Results of the study on the quality of chiffon cakes using stevia instead of granulated sugar It was found that the tasters gave the highest acceptance at 100% in terms of color, taste, texture, and overall liking at the level of very much. When analyzed statistically, it was found that the color and taste were significantly different at the confidence level.